Application of THz Vibrational Spectroscopy to Molecular Characterization and the Theoretical Fundamentals: An Illustration Using Saccharide Molecules. Issue 3 (9th January 2017) - Zhang, Feng; Wang, Houng‐Wei; Tominaga, Keisuke; Hayashi, Michitoshi; Hasunuma, Tomohisa; Kondo, Akihiko
Abstract: This work illustrates several theoretical fundamentals for the application of THz vibrational spectroscopy to molecular characterization in the solid state using two different types of saccharide systems as examples. Four subjects have been specifically addressed: (1) the qualitative differences in the molecular vibrational signatures monitored by THz and mid‐IR vibrational spectroscopy; (2) the selection rules for THz vibrational spectroscopy as applied to crystalline and amorphous systems; (3) a normal mode simulation, using α‐l ‐xylose as an example; and (4) a rigorous mode analysis to quantify the percentage contributions of the intermolecular and intramolecular vibrations to the normal mode of interest. Abstract : Vib‐rational evaluation : Several theoretical fundamentals underpinning the application of THz vibrational spectroscopy to molecular characterization have been qualitatively elucidated. Using crystalline α‐l ‐xylose as an example, the four THz modes have been quantitatively assigned.